Estimating the Potential of Ride Sharing in Urban Areas: the Milan Metropolitan Area Case Study - Anna Realini (SDEWES Centre, 2021)
In the near future, cities will have to supply innovative and high value-added mobility services, that shall be sustainable in terms of environmental impact, traffic management and energy efficiency. This represents a great challenge: transportation accounts for 20% of the global energy consumption, with a large share in urban areas (around 40% of total transport consumption). One of the most promising solutions to reduce congestion, energy consumption and air pollutants in highly-populated areas is Ride Sharing. Ride Sharing systems aim to bring together travellers with similar itineraries and time schedules, thus providing significant societal and environmental benefits, such as reducing the number of cars used for personal travel and improving the utilization of available seat capacity (also defined “occupancy rate”). This paper examines the impact of Ride Sharing by developing an enhanced transport model in Visum, which takes into account the shareability of passengers mobility patterns. The model is applied to the Milan Metropolitan Area, which represents an interesting test case for two main reasons: first, its high population density and strong transport offer and second, the large amount of information and data available on passengers mobility. The paper assumes an optimal 20% participation rate to Ride Sharing and estimates its benefits in terms of congestion reduction, energy efficiency and environmental impact. The COPERT software is used to estimate Carbon Dioxide emissions and fuel consumption savings. The simulation results show that Ride Sharing brings a sort of rebound effect, since there is an increase in passengers traveling by car. However, the overall effect is a reduction in the number of vehicles used, with consequent reductions in vehicle kilometers travelled (-3.8%). This translates into 6% energy savings and 6% Carbon Dioxide emissions reduction. Some policy recommendations are provided to develop Ride Sharing in order to increase the effectiveness of this system while restraining side effects.